Comparison of efficacy of propofol and sevoflurane for laryngeal mask airway insertion during elective surgeries - Rehman, H R; Hassan, I; Hussain, T; Mir, A A; Zahid, M (Journal of Chitwan Medical College, 2015)
This study was conducted in the Department of Anesthesiology, Holy Family Hospital Rawalpindi from 5 October 2011 to 5 April 2012 after approval of hospital ethics committee. Three hundred and eighteen patients fulfilling the inclusion criteria were selected in the study by non-probability consecutive sampling after taking informed written consent. Patients between the ages of 20 to 40 years were included, belonging to ASA class I and II, requiring General Anesthesia with Laryngeal Mask Airway for different surgical procedures. They were divided into two equal groups by computer generated random numbers. Group A comprised of one hundred and fifty eight patients in whom intravenous propofol was given for induction of anesthesia and Laryngeal mask insertion. Group B comprised of one hundred and fifty eight patients in whom inhalational induction with sevoflurane was done for Laryngeal mask insertion. Conduct of anesthesia was maintained similar in both groups. Cough and gag reflexes were observed in both groups at the time of Laryngeal mask insertion. Drug under study was said to be effective, if it is associated with no cough and gag reflex during Laryngeal mask insertion. All the data was analyzed by SPSS version 15. It was observed that 6.3% patients of group A (propofol) had positive cough reflex as compare to 13.2%% patients of group B (sevoflurane). The difference was statistically significant (p=0.038). While the incidence of gag reflex in group A was 8.2% and group B was 14.5%. But the difference was not found to be statistically significant (p=0.077). Propofol is more effective than sevoflurane for smooth LMA insertion during elective surgeries. DOI: http://dx.doi.org/10.3126/jcmc.v5i1.12562